2021
DOI: 10.1111/1462-2920.15416
|View full text |Cite
|
Sign up to set email alerts
|

The infection cushion of Botrytis cinerea: a fungal ‘weapon’ of plant‐biomass destruction

Abstract: The necrotrophic plant-pathogen fungus Botrytis cinerea produces multicellular appressoria dedicated to plant penetration, named infection cushions (IC). A microarray analysis was performed to identify genes upregulated in mature IC. The expression data were validated by RT-qPCR analysis performed in vitro and in planta, proteomic analysis of the IC secretome and biochemical assays. 1231 upregulated genes and 79 up-accumulated proteins were identified. The data support the secretion of effectors by IC: phytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 117 publications
1
40
0
Order By: Relevance
“…This appears to be unique to Lactarius so far, as massive up-regulation of sedolisin genes has not been reported in any other ectomycorrhizal fungi ( Kohler et al, 2015 ; Miyauchi et al, 2020 ). Although a regulation of some sedolisin genes was observed in a few plant-interacting fungi, such as the necrotrophic pathogen Botrytis cinerea , their role(s) in the interaction remain largely unknown ( Choquer et al, 2021 ). However, their dramatic up-regulation observed in the present study and the striking expansion in Lactarius genomes ( Looney et al, 2021 ; Lebreton et al, in preparation), both suggest their involvement in Lactarius symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be unique to Lactarius so far, as massive up-regulation of sedolisin genes has not been reported in any other ectomycorrhizal fungi ( Kohler et al, 2015 ; Miyauchi et al, 2020 ). Although a regulation of some sedolisin genes was observed in a few plant-interacting fungi, such as the necrotrophic pathogen Botrytis cinerea , their role(s) in the interaction remain largely unknown ( Choquer et al, 2021 ). However, their dramatic up-regulation observed in the present study and the striking expansion in Lactarius genomes ( Looney et al, 2021 ; Lebreton et al, in preparation), both suggest their involvement in Lactarius symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, microscopic studies revealed that both the T2.16 and HUB.1 mutants were altered in the production of infection cushions (IC), multicellular appressoria dedicated to the massive secretion of effectors during plant infection ( Mentges et al, 2020 ; Choquer et al, 2021 ). Based on the important role IC play in the virulence of B. cinerea ( de Vallée et al, 2019 ), this default could explain the loss of pathogenicity in these mutants.…”
Section: Discussionmentioning
confidence: 99%
“…When incubated on glass surfaces for two days, WT germlings form large aggregates of appressorialike structures, so-called infection cushions. They are believed to represent alternative infection structures to simple appressoria (Choquer et al 2021). Infection cushions with similar morphology were formed by the WT and the 12xpg and 12xbb mutants (Fig.…”
Section: Phenotypic Analysis Of Multiple Mutants Lacking Up To 12 Cdips and Phytotoxinsmentioning
confidence: 92%